Clipping of Multiple Cerebral Aneurysms Through Cranioorbital Zygomatic Approach: 2-Dimensional Operative Video. Issue 6 (11th September 2021) - Almefty, Rami O; Ibn Essayed, Walid; Al-Mefty, Ossama
Abstract: Ruptured cerebral aneurysm is a grave disease, with a high morbidity and mortality, mandating securing the aneurysm to eliminate fatal rebleeding. 1 Multiple aneurysms are frequent and may occur in approximately 20% of the cases with female prominence. 2 The risk of subarachnoid hemorrhage in unruptured aneurysms is higher in patients who had prior ruptured aneurysms. 3 Hence, there is an indication of treating all concomitant aneurysms when one is ruptured. We present the case of clipping of 3 aneurysms via a cranioobritozygomatic (COZ) approach including a middle cerebral artery, anterior choroidal artery, and superior cerebellar artery in a patient presenting with subarachnoid hemorrhage and multiple aneurysms with suboptimal morphology for endovascular coiling. We highlight the advantages of the COZ in the clipping of complex posterior circulation aneurysms and the advantage of mobilization of neural structures to gain wider exposure. 4-6 The temporal fossa space provided by zygomatic osteotomy allows the outward mobilization of the temporal lobe after freeing it by splitting the Sylvian fissure. The falciform ligament is opened overlying the optic nerve, allowing for safe dissection within the opticocarotid window. The oculomotor nerve is detethered from the dura surrounding its entry into the cavernous sinus. These maneuvers allow for mobilization of the critical neurovascular structures, which widens the operative corridor without undue traction or retraction. The COZ with clinoidectomy shortens and widens the operative field, allows for enhanced maneuverability, improved visualization, and exposure of the clinoidal carotid, and facilitates the release and mobilization of the optic and third nerve. The patient consented to surgery. Image at 1:40 reprinted with permission from Al-Mefty O, Operative Atlas of Meningiomas. Vol 1, © LWW, 1998.